(untitled) (Research, Society and Development, 2021)
This article portrays a case study carried out at Escola Professora Vicentina Campos, in Fortaleza (Ceará), including two classes from the final years of elementary school. Our objectives were: to analyze the use of didactic material (teaching modules) to support the teaching of Mathematics; to compare the performance of students submitted to Mathematics teaching using these teaching modules as a didactic resource, with the performance of students submitted only to traditional teaching. We use the results of a written assessment and our participant observation as a source of data collection. The results showed that the use of educational support material, together with a methodology that enables the construction of significant relationships, contributed with positive aspects relevant to teaching, in addition to providing a better performance of the class that used such modules. This article is the result of a Course Completion Paper (TCC) within the postgraduate course in Mathematics, at the Federal University of Ceará (UFC).